2016
DOI: 10.1097/sle.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Against 2-Dimensional Laparoscopic Colectomy for Right-sided Colon Cancer

Abstract: 3D laparoscopy appears to reduce the performance time of laparoscopic colectomy when compared with 2D laparoscopy. Further studies are required to address the role of the 3D vision system in laparoscopic colectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…The screening process lead to full-text evaluation of 12 studies. Finally, five retrospective comparative studies and one RCT met the predefined criteria and were included in the review (9,(19)(20)(21)(22)(23). Three studies were conducted in China, one in Korea, one in Italy and one in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…The screening process lead to full-text evaluation of 12 studies. Finally, five retrospective comparative studies and one RCT met the predefined criteria and were included in the review (9,(19)(20)(21)(22)(23). Three studies were conducted in China, one in Korea, one in Italy and one in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…This was echoed by another retrospective study by Aykan et al which demonstrated less blood loss in 3D laparoscopic radical prostatectomy (138 vs. 102 mL, P<0.001) (18). However, similar finding was not seen in studies involving other surgical procedures (17,23,24).…”
Section: Clinical Trials On Operative Outcomesmentioning
confidence: 92%
“…With regard to postoperative complication, hospital stay and operative mortality, the current literature did not show any difference between 2D and 3D laparoscopic procedures (17,21,23). For example, Velayutham et al compared 3D and 2D laparoscopic hepatectomy and demonstrated similar complication rates: bile leak (P>0.999), postoperative ascites (P>0.999) and respiratory complications (P=0.544) (24).…”
Section: Clinical Trials On Operative Outcomesmentioning
confidence: 92%
“…Hence, the aim of this study was to determine whether a difference exists on the ability to retrieve 12+ nodes in elective colon cancer colectomies performed open versus laparoscopic. We determined that there are greater odds of retrieving more than 12 LNs with open approach compared to laparoscopic. Additional research is needed to further investigate the specific factors influencing the ability to retrieve an adequate number of LNs, such as viewing angles provided with an open approach versus laparoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies achieved greater than 12 LNs using various procedures, such as laparoscopic complete mesocolic excision (CME), open CME, CME with complete vascular ligation, laparoscopic radical LN dissection including non-regional LNs, robotic surgery, intra-and extracorporeal laparoscopic surgery, single-and multi-port laparoscopic surgery, 2D versus 3D laparoscopic surgery and even a multidisciplinary approach [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%